Reasons for Quitting, Reasons for Relapse, and Knowledge toward the Danger of Smoking in Active Smokers - Burhannudin Ichsan; Yudwari Adhicha Nuredis; Wildan Priscillah (Journal of Health Promotion and Behavior, 2020)
Background: Smoking is a national and world problem. The prevalence of smoking in Indonesia is quite high. Not all smokers have the motivation to quit smoking. Most people who quit smoking have relapse experiences. There have been many advertisements about the dangers of smoking. The dangers of smoking on average are known by everyone, including smokers themselves.Subjects and Method: This study is a quailtative study which intends to determine the reasons for quitting and relapse and their knowledge of the dangers of smoking. The research subjects consisted of 29 people who met the criteria, namely smokers who had quit and then relapsed again in the city of Surakarta.Results: The results showed that the reasons for the respondents to quit smoking were: sickness, not allowed by their parents, no money, a work environment that did not allow them for smoking, having children, reflexes or suddenly wanting to not smoke, wanting to live healthy, because they wanted to register for official school, and because they like sports. Reasons for respondents who had stopped smoking relapsed, namely: recovery from illness, factors from friends and the environment, due to accidentally or suddenly smoking, addiction or dependence, and because of stress. The knowledge of respondents who relapsed from smoking cessation behavior about the dangers of smoking, namely: smoking is a danger, cigarettes can cause cancer, smoking is detrimental to health, smoking can cause lung disease, coughing, shortness of breath, heart, smoking can cause throat disease, smoking can cause stroke, don't know the dangers of smoking, and some say it all depends on God.Conclusion: This study shows that people who return to smoking have a good knowledge of the dangers of smoking. The results of this study indicate that there are factors other than knowledge that influence smoking behavior.Keywords: smoker, quit, relapse, knowledgeCorrespondence: Burhannudin Ichsan. Department of Medical Community/ Public Health, Faculty of Medicine, Universitas Muhammadiyah Surakarta. Komplek Kampus 4 UMS Gonilan Kartasura, Jl. A. Yani Tromol Pos 1 Pabelan Kartasura, Sukoharjo, Surakarta, Central Java, Indonesia. Email: bi268@ums.ac.id. Mobile: 081325495988.Journal of Health Promotion and Behavior (2020), 05(04): 232-239https://doi.org/10.26911/thejhpb.2020.05.04.01.